2008
DOI: 10.1007/s11581-007-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic materials from the visible to the infrared region: an example WO3

Abstract: Herein, the example of the most typical electrochromic material, namely WO 3 , is used to illustrate the potential of electrochromic materials for controlling infrared reflectance and hence, emissivity. Playing with various growth parameters, contrast in reflectance between the inserted H x WO 3 and deinserted WO 3 states as high as 73% in mid-wavelength band (MW, 3-5 μm) was achieved for 320 nm WO 3 films. The latter electrochromic materials were radio frequency sputtered on Au substrate at ambient temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Electrochromic materials have been proved especially useful for smart windows, large‐area information‐displays, rear‐view mirrors for automobiles, energy saving, etc 1–4. The cation intercalation leads to additional electronic states in the bandgap of the materials, which in turn affects a change in the optical properties of the material causing light absorption in the visible spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic materials have been proved especially useful for smart windows, large‐area information‐displays, rear‐view mirrors for automobiles, energy saving, etc 1–4. The cation intercalation leads to additional electronic states in the bandgap of the materials, which in turn affects a change in the optical properties of the material causing light absorption in the visible spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the super‐broadband optical tunability of LTO, device design is also important for a functional electrochromic device. Effective designs for infrared electrochromism with metal substrates have previously been reported in the literature . Here, a proof‐of‐concept of the design shown in Figure f is demonstrated in Figure S8 (Supporting Information).…”
Section: Resultsmentioning
confidence: 73%
“…Such a device would not have leakage issues, and be operable at temperatures beyond the range of existing aqueous designs. [5,7a,8,21] While this study focuses on material properties, further work on in situ electrochromic switching of Li 4 Ti 5 O 12 remains to be done for device applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies indicated a strong dependence of the evolution of the reflectance with the depositions conditions and in particular with the oxygen pressure for RFS-WO 3 thin films [7]. Fixing the pressure to its optimized value, namely 45 mTorr, for both FTO and Au substrates, an increase in film thickness leads to an increase of the optical modulation in the LW band (Table 1).…”
Section: Rfs-wo 3 Thin Film As Single-layermentioning
confidence: 93%